PENYULUHAN MASYARAKAT PESISIR UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT DENGAN CARA PENDEKATAN MANAJEMEN Economic Circular WILAYAH PESISIR - Dwi Agung Saputra (PT. Jurnal Center Indonesia Publisher, 2024)
Observations and observations to seek information on human resources and natural resources in coastal areas to create regional regulations for coastal communities that are integrated with local culture and wisdom that respects culture, customary law and the legal rights of the stakeholders involved. This is important to ensure the implementation of the program in terms of overall development of coastal areas in all fields. Budget planning that is right on target and collective aims to ensure that the plans made will be realized so that the development of coastal areas will be better. By creating data on coastal resources that is implementation-oriented in promoting coastal area management and strategic goals, such as economic development and food security, protecting public health, preventing conflict, and protecting environmental sustainability through coastal resource management.